ANALISIS PENGARUH ROE, FIRM SIZE, CURRENT RATIO DAN DER TERHADAP RETURN DEFENSIVE STOCKS (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2011-2015) - Sakina, Ida; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2017)
The aim of infestation is to look for profit in the future. Defensive stocks are low beta stocks (under 1) which can be made by the investor as an infestation strategy alternative in avoiding risk. This infestation strategy could give profits because the risk itself tend to low (beta under 1) that could give optimal return. This research is done to analyze ROE, firm size, current ratio and DER to return defensive stocks. The secondary data of this research is obtained from defensive manufacture company in period 2011 â€“ 2015. The analytical method that is used in this research is multiple linear regression model by testing classical assumptionn, F statistic test, hypothesis test by using t statistic test Â and coefficient of determination test (R2). The result of this research explains that ROE variable, firm size and current ratio have significant positive impacts to return defensive stocks. The variables in this research have R2 in amount of 24.6% up to 75.4% return defensive stocks that is described by another factor from this research.